Development of Anyflip-Assisted Digital Modules for the Material “My Indonesia is Rich in Culture” - Dita Destiana; Nur Isa Almasiah; Eka Suhardi; M. Afifuddin Khotibul Umam (Journal of General Education and Humanities, 2025)
The limited interactivity of conventional printed modules often impedes the development of students’ critical and analytical thinking skills. This study aimed to design and validate an interactive digital module using the Anyflip platform for the topic “My Indonesia is Rich in Culture”, targeted at fourth-grade elementary students. Utilizing a Research and Development (R&D) method based on the ADDIE model—comprising Analysis, Design, Development, Implementation, and Evaluation—this study involved 25 students from SDN Pabuaran 02, Bogor Regency. The module underwent expert validation and was tested through a pre-test and post-test design. The expert validation yielded an average score of 96.5%, indicating high feasibility and validity. Student responses demonstrated an 80.6% satisfaction rate, and the N-Gain score was 0.60, reflecting a moderate improvement in learning outcomes. These findings indicate that the Anyflip-assisted digital module is a viable and effective tool for enhancing student engagement, motivation, and cultural understanding in elementary education settings.